(untitled) (Filološke studije, 2019)
In the article, the word-formational semantics of noun derivatives in Proto-Slavic is discussed. The word-formational meaning of a noun derivative is, from the synchronic point of view, determined by its word-formational base (verbal root, verb, adjective or noun) as well as by the non-structural noun suffix, which conveys at least one word-formational meaning.